Penerapan Konseling Kelompok Untuk Meningkatkan Kemampuan Interaksi Sosial Siswa - Kristiani, Kristiani (CV. SINAR HOWUHOWU, 2024)
This study aims to determine the effectiveness of applying group counseling in improving students' social interaction skills. Social interaction is a crucial aspect of students' development, influencing their success in school and community environments. This research employs a quasi-experimental method with a pretest-posttest design. The research subjects are high school students who exhibit difficulties in social interaction. The group counseling approach is designed to provide students with opportunities to share experiences, enhance self-confidence, and develop communication skills through guided discussions and collaborative activities. The results of the study indicate a significant improvement in students' social interaction skills after participating in group counseling sessions. This demonstrates that group counseling can be an effective strategy to help students develop healthy social relationships.